Hydrological Information related Existed Dam Sites Assessment using ArcGIS in Zawita District - Klari, Zahraa Mahmood; Abdulrahman, Dadvan Hakeem (Kurdistan Journal of Applied Research, 2022)
One of the critical pillars that sustain human civilization is meeting the water demand for different purposes like storage, electricity, flood control and others. In other hand, the mismanagement of water resources and unplanned urbanization denoted as the most obstacles for developing the arid and semi-arid regions. For this, it is important to know the appropriate places to construct such important projects and to evaluate those places if those places are actually suitable for constructing dams or not. In this paper, a hybrid Geographic information system (ArcGIS) decision-making technology powered by fuzzy logic is developed to assess seven small dams’ sites in the Zawita district. Some standard criteria were used for evaluation like: Rainfall, Geological formations, Types of soil, Slope, Surface hydrological properties, and drainage density. The result all dams within the Zawita district are located in areas with suitable geological formations. It turns out that there are three finished dams that were built in relatively suitable places, they are: Botiya, Bari bhar, and Bhiri. Finally, As for the unfinished dams, one dam is considered an Unsuitable location according to all the criteria used, which is the Talwa dam and one dam within a relatively suitable location, which is the Eminki dam, while the Bisre dam was one of the appropriate dams that has not been built yet.